Protein releasing kinetics of bakers' yeast cells by ultrasound - Apar, D. K.; Ozbek, B. (CROATIAN SOC CHEMICAL ENGINEERING TECHNOLOGY, 2008)
The protein releasing kinetics of Saccharomyces cerevisiae cells were investigated by using the ultrasonication method. The effects of acoustic power, duty cycle % of a sonicator, medium pH and cell concentration on protein release were examined. An attempt was also made to enhance cell disruption further by adding glass beads to the solution. An increase with protein release was observed with increasing acoustic power, duty cycle and glass beads loading %. The protein release was found almost independent of cell concentration and optimum pH was obtained as 7. The relationship between protein release and processing time at various process conditions were studied; and the data were fit to a first order kinetic expression. By using the kinetic data, energy calculations with respect to protein release % were made; and found that using high acoustic power is not feasible for disruption process. By increasing the duty cycle %, no significant energy alteration was observed to achieve the same protein release %. However, disruption time decreased considerably. The effect of ultrasonic energy which is a function of both acoustic power and duty cycle % on the kinetic coefficients was also investigated using an exponential expression based on Arrhenius equation; and the activation energy of protein release was found as 0.44 W L-1.
Keywords: cell disruption; kinetic coefficients; protein release; yeast; sonication process; SACCHAROMYCES-CEREVISIAE; DISRUPTION; ULTRASONICATION; MILL; Biotechnology & Applied Microbiology; Engineering